TANTANGAN MENEMPUH PENDIDIKAN TINGGI: STUDI OPTIMISME DAN RESILIENSI AKADEMIK MAHASISWA PENERIMA BEASISWA BIDIKMISI - Isliko, Eriska Debora; Huwae, Arthur (Program Studi S1 Psikologi, 2023)
Students who want to continue their education at tertiary institutions certainly need a lot of money, many students are vying for scholarships to continue their studies. One of the scholarships that are in great demand is the Bidikmisi scholarship. Being a student who receives a Bidikmisi scholarship certainly has challenges and obstacles in lectures. To overcome these obstacles and demands, students who receive a Bidikmisi scholarship need to have good academic resilience. Optimism is one of the factors in the formation of academic resilience. With an attitude of optimism in students who receive Bidikmisi scholarships, it can make these students carry out their duties and responsibilities in the academic field well. The purpose of this study is to determine the relationship between optimism and academic resilience in students receiving Bidikmisi scholarships. The method used is a quantitative method with a correlational design. The total participants in this study were 110 students receiving Bidikmisi scholarships throughout Indonesia using the incidental sampling technique. This study used the Academic Resilience Scale (α = 0.869) and the Optimism Scale (α = 0.894). The results of this study indicate a positive relationship between optimism and academic resilience (r=0.366 and sig. = 0.000). That is, the higher the optimism of students, the higher the academic resilience of students receiving bidikmisi scholarships.